GC-MS and FTIR characterization of 1,3,4-oxadiazole from Biophytum sensitivum with potential cardiovascular applications - Richard, Jasmine Juliet; Annapoorani, Ponnambalam; Mariappan, P. (Current Botany, 2024)
Cardiovascular diseases (CVDs) remain a leading cause of mortality worldwide, with a rising burden in low- and middle-income countries such as India. As concerns grow over the side effects and long-term safety of synthetic drugs, plant-derived bioactive compounds are gaining attention for their therapeutic potential. In this study, the traditional medicinal plant Biophytum sensitivum (L.) DC was investigated for its cardioprotective phytoconstituents. Methanolic (MeOH) extracts of the whole plant were first analyzed using Fourier Transform Infrared Spectroscopy (FTIR), which revealed key functional groups including hydroxyl, ester carbonyl, aromatic, and nitrogenous moieties-features commonly associated with antioxidant and lipid-regulatory activity. Subsequent Gas Chromatography–Mass Spectrometry (GC-MS) profiling identified several secondary metabolites, including two prominent oxadiazole derivatives: 2-p-nitrophenyl-5-isopropyloxy-1,3,4-oxadiazole-5-one and 1,2,5-oxadiazole-3-amine-4-(4-methoxyphenoxy). These heterocyclic compounds are associated with lipid-lowering, calcium channel-modulating, and anti-inflammatory properties, supporting the plant’s therapeutic potential. The findings validate the ethnomedicinal use of B. sensitivum and highlight its promise as a natural source of bioactive molecules for developing safer cardiovascular drugs.